Receiver design for MIMO FSO communication systems with photon-counting detection. (c2019) - Mawla, Rami Issam El (2019)
Optical wireless communication (OWC) constitutes a key technology for 5G wireless networks. OWC alleviates the radio frequency (RF) spectrum crunch problem by enabling communications in the visible, infrared and ultraviolet optical frequency bands for a variety of indoor and outdoor applications. Outdoor infrared OWC systems are widely referred to as free-space optical (FSO) communications that rely on line-of-sight transmissions of narrow laser beams. The FSO technology is license-free, easy-to-deploy, cost-effective and capable of delivering very high data rates. The major impairment that severely degrades the performance of FSO links is related to the random aspect of the atmosphere. Overcoming atmospheric turbulence-induced fading became the key research area where many solutions have been proposed and analyzed. These solutions include the multiple-input-multiple-output (MIMO) techniques. This work investigates and compares three MIMO FSO techniques; namely, spatial-multiplexing (SMux), repetition-coding (RC) and optical-spatialmodulation (OSM). Unlike the existing literature that considers the simplistic additive white Gaussian noise (AWGN) model, this work revolves around the more accurate Poisson noise model where the number of detected photons at the receiver follows the Poisson distribution for shot-noise limited receivers. We compare the SMux, RC and OSM systems in terms of data-rate, error-rate, receiver complexity, channel estimation requirements… For each system, the optimal maximum-likelihood (ML) decoder is derived and analyzed under Poisson noise. We also evaluate the theoretical bit error rates (BERs) of RC and OSM. While the SMux and RC schemes are the most efficient in terms of maximizing the data-rate and minimizing the error-rate, respectively, the OSM scheme constitutes a practical appealing tradeoff between SMux and RC. The OSM solution leverages the need for inter-antenna synchronization while achieving improved multiplexing gains.